Implementasi Metode Pembelajaran Media Gambar Untuk Meningkatkan Kemampuan Menulis Siswa Kelas II SDN 1 Pemenang Barat Tahun Ajaran 2023/2024 - Sari, Devi Ratna; Hadi, Rusman; Jannah, Rauhun (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2024)
This research is to describe the implementation of the graphic media learning method applied by class II teachers at SDN 1 Juara Barat. This research was carried out at SDN 1 Juara Barat District in class II of SDN 1 Juara Barat in the 2023/2024 school year. The method used in this research is a qualitative approach and in terms of method it is a descriptive method. Data collection techniques use observation, interviews and documentation techniques. The data sources for this research are school principals, teachers and students. And the data analysis techniques used in this research are data collection, data reduction, presentation and drawing conclusions. The results of the research show that (1) Implementation of the visual media learning method to improve the writing skills of class II students at SDN 1 Juara Barat was carried out by a) The teacher directing students to read first, getting into the habit of reading, b) Providing visual type learning media that can support the process. learning activities by choosing media that is as interesting as possible so that students are interested in participating in learning activities by paying attention to learning objectives. c) Using the practice learning method is necessary to make it easier for students to understand the learning material and the teaching and learning process can run smoothly and effectively. (2). The obstacles faced by teachers in improving the writing skills of grade 2 students at SDN 1 Juara Barat for the 2024 academic year are the lack of students' ability to string and arrange random letters into perfect vocabulary, low student interest in reading and low student interest in learning. The teacher has tried several things to find out the obstacles and solutions carried out by the teacher as a result of which the students' ability to write narrative essays can improve.